TREND OF IRRATIONAL MEDICATION AMONG THE STUDENTS OF DEPARTMENT OF PHARMACY ABBOTTABAD UNIVERSITY OF SCIENCE AND TECHNOLOGY IN COMMON COLD AND FLU - Rehman, Mujeeb Ur; Mehsud, Saif Ullah; Ishaq, Muhammad; Khan, Mumtaz Ali; Ali, Sartaj (Journal of Ayub Medical College Abbottabad, 2017)
Background: Common cold and flu are mostly of viral pathogenesis with symptoms in upper respiratory tract. It is highly contagious and close inter-individual contact in winter season increase the spread spectrum. Mis-interpretation with bacterial cause leads to irrationality in its medication. Methods: A cross-sectional study was conducted among pharmacy department students in February-March 2016. Data were collected through self-administered questionnaire and expressed as percentage frequency. Results: Total 180 students were provided with questionnaire to fill the desired data. 66 out of them were reported as patients of common cold and flu. Trend of medication after compilation and analyzing data reveal that: 60.60%(n=40/66) students got irrational medication, 4.54% (n=3/66) students presents with other disease, so were declared of complex nature and 9.1% (n=6/66) patients, presented only with symptoms were counseled accordingly to the standard therapy by Health Protection Agency-UK (Management of infection guidance for primary care for consultation and local adaptation, 2013), and Columbia University Medical Center (Guidelines for the empiric use of antibiotics in adult patients - Feb, 2005) and all of them were followed for their entire therapy time. All of the counseled patients recovered successfully. Total 25.76% (n=17/66) other than that of counseled group students also got rational medication. Conclusion: Use of medicine by students in study was found irrational. National and international awareness programs about such viral disease should be designed and arranged to promote information in the community and limit the irrational medication. It also need an active health regulatory authority in undeveloped and less developed countries specially to limit the availability of prescription drugs without physician advise through availability of qualified person in pharmacies. Keywords: Rational medication; Common cold; Flu, Self-medication